THE IMPLEMENTATION OF MENTAL HEALTH POLICY AND LEGISLATION: IS DEINSTITUTIONALISATION A PREDICAMENT FOR SOCIAL WORKERS AND FAMILIES? - September, Uwarren; Strydom, Marianne (Social Work/Maatskaplike Werk, 2024)
Globally, policy and legislation on mental health have shifted towards deinstitutionalisation. South African policy and legislation were adapted to adhere to international policy directives, resulting in a strong emphasis on reintegrating people with mental illness into their families and communities. The practical implementation of this shift depends on the existence of community-based organisations to support families and persons with mental illness. However, no research is available on the view of social workers on the implementation of mental health policy and legislation and the possible challenges experienced with deinstitutionalisation. To investigate if deinstitutionalisation presented a predicament for social workers and families, a qualitative approach – with exploratory and descriptive research designs – was employed with social workers and their supervisors working at selected psychiatric hospitals. These participants were approached specifically because they are often at the frontline of implementing mental health policy and legislation. It was concluded that existing legislation was superficial, unknown and patient-driven, and that deinstitutionalisation was viewed as an ineffective reintegration strategy. Recommendations are that policymakers must reassess the implications of this legislation and address community-based resources to support the proper deinstitutionalisation of and care for people with mental illness and their families.